Університетська клініка як чинник забезпечення якості медичної освіти: управлінський аспект - Гукова-Кушнір, Гретта Євгенівна; Gukova-Kushnir, Gretta Yevgenivna (Видавництво Львівської політехніки, 2023)
У статті проаналізовано функціонування університетської клініки як чинника забезпечення якості медичної освіти. Виявлено, що університетська клініка забезпечує високу якість надання медичної допомоги та створює умови для забезпечення якісної освіти медичних працівників. Запропоновано створення та/або удосконалення створених університетських клінік з метою підвищення якості медичної освіти в Україні.

The article analyzes the functioning of the university clinic as a factor in ensuring the quality of medical education. It was found that the university clique ensures high quality of medical care and creates conditions for quality education of medical workers. It is proposed to create and/or improve established university clinics in order to improve the quality of medical education in Ukraine. The functioning of the network of university clinics as structural subdivisions of institutions of higher medical education significantly increases the quality of training of medical students, interns, clinical training, retraining and advanced training of specialist doctors; increases the efficiency of research works and ensures the implementation of their results in practical medicine, as a result of which the quality of providing medical care to the population increases. In such clinics, appropriate conditions are created for the clinical training and retraining of students, medical and scientific-pedagogical workers within the framework of training programs of the system of continuous professional development, improvement and implementation of training programs in internship, master's degree, clinical residency, participation in the development and implementation of programs for improving medical qualifications employees The training of scientific and pedagogical staff of a clinical profile in post-graduate and doctoral studies and improvement of their qualifications is also provided.
The university clinic as a factor in ensuring the quality of medical education: administrative aspect
Keywords: управління; університетська клініка; медичні працівники; якість медичної освіти; якість надання медичної допомоги; міжнародний досвід; management; university clinic; medical workers; quality of medical education; quality of medical care; international experience; 351.77; 614.212; 378.014.61(477)